Wild-type circadian rhythmicity is dependent on closely spaced E boxes in the Drosophila timeless promoter. - McDonald, M.J.; Rosbash, M.; Emery, P. (Molecular and Cellular Biology, 2001)
Transcriptional regulation plays an important role in Drosophila melanogaster circadian rhythms. The period promoter has been well studied, but the timeless promoter has not been analyzed in detail. Mutagenesis of the canonical E box in the timeless promoter reduces but does not eliminate timeless mRNA cycling or locomotor activity rhythms. This is because there are at least two other cis-acting elements close to the canonical E box, which can also be transactivated by the circadian transcription factor dCLOCK. These E-box-like sequences cooperate with the canonical E-box element to promote high-amplitude transcription, which is necessary for wild-type rhythmicity.